The role of aripiprazole in improvement of penile erection in schizophrenia patients with erectile dysfunction - Debby Handayati Harahap; Carla Raymondalexas Marchira; Eti Nurwening Solikhah; Dicky Moch Rizal (Medicinski glasnik, 2021)
Aim: To provide evidence regarding the effectiveness of aripiprazole in improving penile erection with a therapeutic strategy of add-on or switching therapy in patients with schizophrenia. Methods: PubMed, Cochrane, Clinical Key, ProQuest, EBSCOhost, and ScienceDirect were searched for any design study that evaluated aripiprazole only or versus control (placebo or other antipsychotic) for erectile dysfunction in patients with schizophrenia. Three studies were identified and analysed from 295 initial articles. Data were then extracted from the studies and summarized descriptively. Results: Two hundred ninety-five articles were screened, and three studies were identified and eventually selected. After the add-on or switching antipsychotic therapy to aripiprazole, the prevalence of erectile dysfunction and the score of erectile dysfunction or penile erection assessed by Nagoya and Sexual Function Questionnaire (NSFQ) and Arizona Sexual Experience Scale (ASEX) decreased. Conclusion: Aripiprazole was effective to improve penile erectile function in patients with schizophrenia. The therapeutic strategy is adjunctive treatment or switching therapy to aripiprazole.
Keywords: penile erection; prevalence; schizophrenia; sexual behaviour